The Role of Digital Media in the Preservation of Betawi Culture in the @Jakartatourism YouTube Channel - Mashuri, Fath; Nurhayati, Dian; Muharman, Deddy (Institut Komunikasi dan Bisnis LSPR, 2024)
Betawi culture, as the dominant ethnic heritage in Jakarta, has a uniqueness and richness that reflects its long history and interaction with various ethnic and colonial groups. This research is motivated by the need to understand the historical and cultural characteristics of Betawi that have formed the identity of the community. This study aims to analyze the historical and cultural characteristics of Betawi, focusing on how historical, social, and cultural factors have shaped the identity of Betawi society. This research uses a qualitative descriptive approach to explore and understand various key elements of Betawi culture, including language, customs, art, and culinary. The result of the research is that the history of Betawi began from the time of the Sunda Kingdom and the Demak Sultanate, which provided the initial framework for the formation of this society. The arrival of the Dutch in the 17th century brought significant changes, including the introduction of a new administrative system and the transformation of the city of Jakarta into a center of international trade. This colonial influence introduced elements of Western culture that are still visible in the daily life of the Betawi people today. Meanwhile, the formation of the identity of the Betawi tribal community is based on historical, social, and cultural factors that interact with each other to form the identity of the current Betawi community.